Not Just Full-Text Articles: Comparing the Search Function Among Chemistry Electronic Journals' Web Sites - Song Yu (Issues in Science and Technology Librarianship, 2004)
Nearly every electronic journal's web site offers a "Search" function for its users in addition to supplying tables of contents and full-text access to articles. The purpose of this study was to analyze and compare the search features on five chemistry journal publishers' web sites to which Purdue University has full-text access. We compared the search interface, search capabilities, and the output and display. We found that although the "Search" functions on all of the five web sites are not as powerful as those of commercial databases, they offer an efficient way for the users to perform a citation or bibliographic search.